Short stature and insulin-like growth Factor-I in neurofibromatosis Type I (Annals of Medical Research, 2021)
Aim: Certain NF1 patients have short stature due to unclear pathogenesis mechanisms. The aim of this study is to investigate endocrinology parameters which could affect height in NF1.Materials and Methods: Clinical data of 48 NF1 patients aged 19 months to 18 years were collected by reviewing medical records. Current physical examination findings including height, weight, and pubertal status were recorded. Serum samples were obtained from all subjects for follicle stimulating hormone (FSH), luteinizing hormone (LH), thyroid stimulating hormone (TSH), free T4 (FT4), free T3 insulin-like growth factor (IGF1), and insulin-like growth binding protein3 (IGFBP3) levels.Results: Of the 48 patients, 34 (70%) had height below 50 percentiles. Short stature, defined as height
Keywords: Endocrinology; growth; height; IGF-1; neurofibromatosis type I; thyroid